PERAN WANITA DALAM KABA - Hermawan Hermawan; Misra Nofrita (JURNAL PENDIDIKAN ROKANIA, 2021)
This research exposes woman profile derives in Minangkabau Kaba as one of traditional literature works of Minangkabau. The aim to exposes woman profile derives from an idea that woman in Minangkabau have vital role because its social system is matrilineal and literature work is a reflection of its social life. Therefore, woman profile is also expressed in the Kaba. To respond the above paradigm, the researcher choose the Kaba with the following samples: (1) Cindua Mato Kaba of M. Yusuf's philologic work under title 'Transliteration Problem and Story Edition of Tuanku Nan Muda Pagaruyung (Cindua Mato Kaba)', (2) Anggun Nan Tungga Kaba of Ambas Mahkota's work, (3) Malin Deman Kaba of Nurizzati's philologic work under title 'Malin Deman Raba: A Philologic Study'. This choice is based upon a consideration that the above three Kaba can be said as a representative to illustrate or to represent the .existing Minangkabau Kabas. The kabas which are taken as samples of this research are still sung orally and printed many times up to now in the form of publication. To achieve the aim of this research, some approaches of literature sociology and psychology are used. A Kaba as a literature work is regarded as a 'reflection' of society; and therefore what is expressed through the kaba can not be rid of social condition as its background. Based on the above theory, the result of this research shows that woman roles in family as a wife, mother, child, older sister, younger sister, and grandmother. In society, a woman roles as a leader of family and member of society such as household servant, birth shaman, businesswoman or manager of flower garden, foster mother, clothes drier, or local pastoralist. Woman profile in the Kaba has a close connection with individual personally of society according to Minangkabau social system. Moreover, woman in the Kaba role in giving initiation or inauguration to members of Minangkabau society.